Aligning Sustainable Finance and Fintech to Promote an Integrated Approach to Refugee Finance - Dalal Aassouli (16960260) (2025)
The paper aims to assess the global landscape of refugee finance with an overview of global refugee‐related financing mechanisms and instruments. Despite the growing refugee population worldwide, most refugee financing mechanisms are characterized by their post hoc, grant‐based, small‐scale, short‐term, and unpredictable nature. This study will analyze the quantum of refugee finance supplied by different donors and intermediary types, the instruments through which they deploy refugee finance, and to where this financing is directed. It will then evaluate their effectiveness in addressing refugee financial inclusion and empowerment. The paper finally suggests alternative instruments and financing mechanisms leveraging Islamic finance, sustainable finance, and fintech. Two key mechanisms are proposed: a Refugee Empowerment Sukuk and a blended finance structure adopting a results‐based financing approach. The study recommends developing a proactive approach using event‐based financing with early warning triggers, leveraging fintech solutions for traceability and efficiency, and scaling up result‐based financing in social impact and humanitarian financing. Other Information Published in: Global Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/1758-5899.13482